2008
DOI: 10.1021/mp800183b
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Vector Encoding hVEGF and hIL-1Ra for ex Vivo Transduction into Human Islets

Abstract: Ex vivo gene transfer can improve the outcome of islet transplantation for treating type I diabetes. Earlier we have shown co-expression of human vascular endothelial growth factor (hVEGF) and human interleukin-1 receptor antagonist (hIL-1Ra) after transfection of plasmid DNA encoding these two genes. Due to poor transfection efficiency of plasmid DNA and the better known islet transduction efficiency of adenoviral (Adv) vectors, in this study, we constructed Adv-hVEGF-hIL-1Ra by cloning hVEGF and hIL-1Ra codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 34 publications
6
41
0
Order By: Relevance
“…Although these factors were also proven to be helpful in preserving the beta cell mass in T1D animals [11,12], they were absent from the intrinsic pathways governing the development and proliferation of pancreatic beta cells. Therefore, instead of working specifically on pancreatic beta cells, these factors seemed to work predominantly through combination with the native mechanism of beta cell regeneration in a synergistic or additive manner [12,13].…”
mentioning
confidence: 99%
“…Although these factors were also proven to be helpful in preserving the beta cell mass in T1D animals [11,12], they were absent from the intrinsic pathways governing the development and proliferation of pancreatic beta cells. Therefore, instead of working specifically on pancreatic beta cells, these factors seemed to work predominantly through combination with the native mechanism of beta cell regeneration in a synergistic or additive manner [12,13].…”
mentioning
confidence: 99%
“…Immunosuppressive regimens are capable of preventing immune rejection from months to years, but the agents used in these treatments may induce significant side effects, resulting in progressive decline in graft function. Some of the most commonly used immunosuppressive agents such as tacrolimus (also known as FK-506 or Fujimycin), mycophenolic acid (MPA), and sirolimus (also known as rapamycin) are also deleterious to islet function and insulin secretion [4,5]. PNF is characterized as the loss of islet viability and function caused by non-immune reactions, such as the disruption of islet microvasculature during islet isolation and purification process, hypoxia in the core of islet grafts and production of inflammatory cytokines at the transplantation sites.…”
Section: Challenges Of Human Islet Transplantationmentioning
confidence: 99%
“…For example, Giannoukakis et al first reported that adenoviral gene transfer of interleukin 1 receptor antagonist (IL-1Ra) prevented IL-1β-mediated nitric oxide production from human islets in vitro as well as the suppression of insulinproducing β cell function as determined by glucose-stimulated insulin production [3]. In our lab, Narang et al and Panakanti et al combined the gene expression of vascular endothelia growth factor (VEGF) and IL-1Ra to improve the therapeutic effects of single gene therapy while Li et al and Cheng et al targeted downstream pro-apoptotic factors of IL-1β pathway and used small heparin RNA to inhibit the expression of iNOS and caspase 3, respectively [4][5][6][7]. During the time we worked on the apoptosis of human islets, we identified a potent anti-apoptotic factor X-linked inhibitor of apoptosis (XIAP), which binds to and inhibits caspase 3, 7 and 9 at the same time.…”
Section: Progress In Gene Therapymentioning
confidence: 99%
See 2 more Smart Citations